CONSUMER’S PERCEPTION ON INFORMATION AND COMMUNICATION TECHNOLOGIES ( ICT ) WITH SPECIAL REFERENCE TO ICICI KULASKEKHARAM (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
ICT stands for "Information and Communication Technologies". It refers to technologiesthat provide access to information through telecommunication . It is similar to informationtechnology (IT) but focuses primarily on communication technologies. This includes the internet,wireless network, cell phone and other communication medium. ICT technological development,particularly in the area of telecommunication technologies revolutionizing the banking industry,It is widely believed that the impact of e-commerce enables banks to provide an inexpensive anddirect way of exchanging information and to sell or buy product and services. Hence the presentstudy deals with customers' perception on the use of ICT with special reference to ICICI bank inkulashekharam